Coronaviruses in diarrheic pigeons and the first determination of the complete genome of a new pigeon gammacoronavirus - Łukaszuk, Ewa; Dziewulska, Daria; Varsani, Arvind; Stenzel, Tomasz (Scientific reports, 2025)
Members of Orthocoronavirinae subfamily are common among avian species and responsible for diseases in poultry. Unfortunately, knowledge of their diversity and potential pathogenic influence in pigeons is so far scarce. This study describes the first determination of a complete genomic sequence of a member of Gammacoronavirus genus in pigeons, likely representing new species within the Igacovirus subgenus. The newly obtained sequence appears to be closely related to partial gammacoronavirus sequences identified in pigeons from Poland, Spain, Finland and China, which highlights the wide geographical distribution of this virus. Direct quantitative analysis was performed in sampled pigeons to assess the potential connection of the presence of the virus and the occurrence of enteric disease, and while no statistically significant difference in the viral genome copy numbers was found between the diseased and healthy group, the similar detection rate in both groups is noteworthy. This result obtained from the analysis of 153 cloacal swab samples suggests that the presence of the virus likely is not associated with the occurrence of disease in their host. The study accentuates the need to further study the coronaviruses of avian origin especially considering the seemingly often occurrence of asymptomatic coronaviral infections and their broad geographical distribution.